STUDI OPTIMASI PERFORMA PRODUKSI DAN SURFACTANT FLOODING DENGAN SUMUR PRODUKSI HORIZONTAL DAN VARIASI POSISI-JUMLAH SUMUR INJEKSI PADA RESERVOIR MIRING - Giovanni, Irsyad
Reservoir structure which has a slope (dipping reservoir) will affect the performance of oil production. So it is necessary for production planning strategies, especially regarding the optimization of the position and location of injection wells that would affect the sweep efficiency. It also conducted a study on the effect of distance between the horizontal production wells with injection wells that was applied to the dipping reservoir. And then, the study followed by surfactant injection and the result will be compared with water injection. Surfactant injection is one of EOR methods that are used to reduce the surface tension between oil and water so that oil can flow easier. Simulations was conducted by making 3 different reservoir width with a slope angle of 20 º. Each model has two horizontal production wells located on each side of reservoir and injection wells between the two horizontal wells. From this study, we can consider the increasing oil recovery by production optimizing and surfactant flooding.